The one & only a novel - Giffin, Emily (Ballantine Books, 2014)
Centering her life on the successful Walker family, into which she plans to marry, Shea struggles to end her affair with a less-than-stellar boyfriend only to have her entire existence placed in question by the death of the family's mother.